National Ground Water Association's illustrated glossary of ground water industry terms : hydrogeology, geophysics, borehole construction, and water conditioning. (NGWA Press, 2003)
The National Ground Water Association has culminated its various glossaries into a single volume. This collection of words, terms, and phrases was compiled through direct communication with water well and environmental contractors. Many of the terms are slang expressions for various activities, people, or situations around a water well drilling site, while other terms represent the actual or formal name of the well drilling equipment or activity. This glossary is not an all-inclusive documentation of a new dialect, but rather a compilation of phrases and terms that are commonly heard during ground water contracting operations.